Desenvolvimento de ferramentas sorologicas e moleculares para identificação de vírus em videiras e cochonilhas, alterações fisiológicas e na qualidade enológica da uva de videiras infectadas - Basso, Marcos Fernando (2010)
The grapevine (Vitis spp.) being vegetatively propagated facilitates the spread of viruses. In general, viruses are able to induce disorders in plant cells including photosynthesis and metabolic changes, causing alterations in grape quality. The purpose of Chapter I was to identify and molecularly characterize the viruses present in vector mealybugs in two establised vineyards (Rio Grande do Sul, Brazil), one of cv. Cabernet Sauvignon (Vitis vinifera), cultivated since 1995, and the of cv. Isabel (V. labrusca), cultivated since 1971. Plants were checked serologically for six viruses detected. Fragments that comprise complete or partial viral genes were amplified by RT-PCR using 17 pairs of specific primers for detection of the following viruses: Grapevine virus A (GVA), Grapevine virus B (GVB), Grapevine virus D (GVD), Grapevine fleck virus (GFkV), Grapevine fanleaf virus (GFLV), Arabis mosaic virus (ArMV), Grapevine chrome mosaic virus (GCMV), Rupestris stem pitting-associated virus (RSPaV) and Grapevine leafroll-associated virus 1-4 (GLRaV-1 to - 4). Degenerate primers were used for detection of Closterovirus, Trichovirus and Vitivirus genera and Betaflexiviridae family. For each primer pair at least one amplicon was cloned and sequenced, identifying seven isolates of RSPaV, three isolates of GLRaV-2 and two isolates of GLRaV-3. The obtained sequences (submitted to GenBank) showed identities higher than 90% with the homologous viral isolates from the GenBank. GVA, GVB and GLRaV-3 were detected in three of five samples of mealybugs collected in Caxias do Sul (RS) and Petrolina (PE) vineyards. High genetic variability of RSPaV and unavailability of commercial antiserum have impaired the detection of this virus in grapevines. In Chapter II the objective was to produce polyclonal antiserum against the recombinant coat protein (CP) of RSPaV. The complete CP gene of this virus was amplified, cloned, sequenced and subcloned into expression vector pRSET-B, and the recombinant plasmid was used for expression in Escherichia coli cells (strain BL21:DE3). The yield of RSPaV CP, expressed per ml of culture, was 17.35 μg for rabbit immunization 2.55 mg were used. The antiserum showed a concentration of 1939 mg IgG/ml which was able to recognize the recombinant protein in Western blot and detect RSPaV in grapevine infected tissues using the indirect ELISA technique. In Chapter III physiological alterations of plant and enological quality changes of the grapes from infected grapevines GLRaV-2 and RSPaV infected were studied. For these evaluations the photosynthetic potential, total chlorophyll (a and b), total soluble sugars and starch were determined in leaves. Healthy or asymptomatic leaves showed favourable values for almost all characteristics. The saturation photosynthesis was 2.9 (C. Franc) and 2.25 (C. Sauvignon) times higher in healthy than in infected grapevines. Considering the grape quality significant differences between grapes from infected and non-infected grapevine were also observed in five from six characteristics studied. Healthy grapes showed 17.88 (cv. C. Franc) and 16.10 (cv. C. Sauvignon) oBrix values while infected showed 15.35 and 13.38, respectively. Therefore, these viruses can damage the productivity and quality production of these grape cultivars.